METODE BIMBINGAN PENYULUH AGAMA ISLAM TERHADAP LANSIA DI BALAI REHABILITASI SOSIAL LANJUT USIA (BRSLU) GAU MABAJI KABUPATEN GOWA - Safirah, Putri; Syamsidar; Mandjarreki, Sakaruddin (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
The journal created aims to describe how the method of guidance of Islamic religious instructors for the elderly. This study uses the type of descriptive qualitative research located at the Elderly Social Rehabilitation Center (BRSLU) Gau Mabaji, Gowa Regency. The research approach used is the guidance approach. The primary data source of this research is Muminati Puji as a Religious instructor at BRSLU Gau Mabaji, Gowa Regency (key informant), informant’s additional ones are Puji, Sugiati Hartati, Ramli, Rayana, Ahmad, Abdullah Hafid (elderly). Secondary data sources are books, theses, journals, literature, and other data sources that can be used as a complement. Data collection methods are observation, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, presentation of data, and drawing conclusions. Based on the results of this study, the factors that underlie the Islamic Religion instructor in applying the method of guidance to the elderly at the Social Rehabilitation Center Elderly (BRSLU) Gau Mabaji, Gowa Regency, there are two factors, namely: internal factors which include changes in family structure, socialization factors for the elderly, and lonely. Then, external factors which include services and facilities at Balai dan factor no one pays attention to. Efforts of extension workers in Islam in Islam provide guidance to the elderly using the direct method, namely by providing individual guidance such as providing material on Taharah, sitting prayers, standing prayer, types of najis, and how to clean it. This activity is carried out once a week every Tuesday